Hypoxia inducible factor-1α: Its role in colorectal carcinogenesis and metastasis. Issue 1 (28th September 2015) - Nagaraju, Ganji Purnachandra; Bramhachari, Pallaval Veera; Raghu, Godi; El-Rayes, Bassel F.
Highlights: Colorectal cancer (CRC) growth is associated with the physiological state of hypoxia. Hypoxia-stabilized HIF1α is a key factor for CRC metastasis. HIF1α is stabilized by oxygen homeostasis, HSP90 and STAT3. HIF1α in CRC can be targeted by HSP90/STAT3 inhibitors and NSAIDS. Abstract: Tumor growth creates a hypoxic microenvironment, which promotes angiogenesis and aggressive tumor growth and invasion. HIF1α is a central molecule involved in mediating these effects of hypoxia. In colorectal cancer (CRC), hypoxia stabilizes the transcription factor HIF1α, leading to the expression of genes that are involved in tumor vascularization, metastasis/migration, cell survival and chemo-resistance. Therefore, HIF1α is a rational target for the development of new therapeutics for CRC. This article reviews the central role of HIF1α in CRC angiogenesis, metastasis, and progression as well as the strategies to target HIF1α stabilization.